The Influence of Competence, Knowledge and Attitudes of Midwives on The Implementation of Cervical Cancer Prevention Programs at Tangerang Hospital - Linda Mirawati; Cri Sajjana Prajna Wekadigunawan; Kemala Rita Wahidi (Jurnal Health Sains, 2022)
According to the World Health Organization (WHO), cervical cancer is caused by infection with the HPV (Human Papilloma Virus) virus that does not heal for a long time. If the immune system is reduced, then this infection can be malignant (pathogenic) and cause cervical cancer. Prior to 1930, cervical cancer was still the main cause of death for women and cases dropped drastically since the introduction of the Pap smear screening technique by Papanicolauo in 1934, there had been a lot of progress so that in the United States and Western Europe, the incidence of cervical cancer had decreased. "To determine the effect of competence, knowledge and attitudes of midwives on the implementation of cervical cancer prevention programs at Tangerang General Hospital". Is a quantitative research, with a non-experimental research design. This study used analytic regressive method with a cross sectional survey research design to determine the effect of the competence, knowledge and attitudes of midwives working with cervical cancer prevention programs at Tangerang General Hospital. The results of the analysis of the hypothesis test showed that there was a partial influence of knowledge and attitude competence on cervical cancer prevention programs, where the significant value was P = 0.000, which was smaller than P = 0.005. Meanwhile, attitude does not have a significant effect on cervical cancer prevention programs where the P value = 0.354.